2008
DOI: 10.1007/s11259-008-9060-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of biotin supplementation on hoof health and ceramide composition in dairy cattle

Abstract: The effect of biotin supplementation on various foot lesions and hoof ceramide composition of toe (wall) and sole portions of hooves was studied in crossbred dairy cattle. Biotin supplementation was done for five months in 14 cattle at a farm and the other 14 animals kept as control. A significant decline was observed in heel erosions and sole avulsions along with total disappearance of white line fissures and double soles in the biotin supplemented cattle resulting in decrease in the overall disease score. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
2
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 20 publications
(19 reference statements)
1
19
2
1
Order By: Relevance
“…The rear leg view index of each animal was observed as normal (score 0) when there was no inward knuckling of the hocks when seen from the rear and as cow hock (score 1) when there was inward knuckling of the hocks observed from the rear (RANDHAWA et al, 2008). Body condition score was evaluated on a five-point scale as described by FERGUSON et al (1994).…”
Section: Selection Of Animals and Management Practices The Study Invmentioning
confidence: 99%
“…The rear leg view index of each animal was observed as normal (score 0) when there was no inward knuckling of the hocks when seen from the rear and as cow hock (score 1) when there was inward knuckling of the hocks observed from the rear (RANDHAWA et al, 2008). Body condition score was evaluated on a five-point scale as described by FERGUSON et al (1994).…”
Section: Selection Of Animals and Management Practices The Study Invmentioning
confidence: 99%
“…However, despite the production of a better quality corneal tissue due to biotin, the environmental hygiene conditions to which the animals were exposed remained unchanged. A similar justification was presented by Randhawa et al (2008) upon observation that the supplementation with biotin did not influence recovery of the more severe lesions in the hoof; however, the authors did not relate this to the deficit in environmental hygiene. The period during which the animals were supplemented with biotin must also be considered.…”
Section: Discussionmentioning
confidence: 65%
“…Bergsten et al (2003) observed the positive effect of biotin supplementation on the production of milk, and the reduction of digital lesions in dairy cows. Randhawa et al (2008) evaluated the intensity and prevalence of several digital lesions in a single group of dairy cows prior to and after supplementation with biotin. These researchers proposed the prevention and treatment of foot lesions with biotin to be due to its participation in protein synthesis, which enhances the keratinization of epidermal adnexa, including the hoof corneal case.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…II, 347, 348, 350, 416, 430, 466. 63 Cf. for example Randhawa and Randhawa 1985; also Khandalavala 1991 provides a useful survey, from which the paucity of the floating celestials in Mathurān art in this period may be derived 64 Grünwedel 191265 Juliano 2001Tucker 2003, 155; The margin for error with carbon dating leaves a 4th century dating viable. This seems more in accord with other evidence (oral information by Dr. Kurt Behrendt)…”
mentioning
confidence: 99%